Effect of incorporating food-grade lactic acid in minced beef on storage stability and sensory evaluation of the produced patties - M. Abd Elgadir; A. A. Mariod (Теория и практика переработки мяса, 2024)
The objective of this research is to evaluate quality properties and storage stability of beef patties formulated from fresh beef incorporated with food-grade lactic acid (LA). Fresh beef was purchased from the local market immediately after slaughter, minced and formulated using water incorporated with food-grade lactic acid in concentrations of 0.0% (control); 0.5%; 0.75% and 1.00%. The LA-incorporated formulations were used in the preparation of the patties. The prepared patties were stored at a refrigeration temperature of 5 ºC for 12 days. pH, instrumental color, texture profile analysis (TPA), water activity and total viable count (TVC) were investigated. At the end of the storage period, the patties were cooked and sensory evaluated. The results revealed a significant (p ≤ 0.05) decrease in pH of the control patties from 6.2 ± 0.1 to 5.1 ± 0.2–5.4 ± 0.2 from day 8 to day 12 of the storage time. The same trend was observed in the LA-incorporated patties. The LA-incorporated patties did not show any significant differences (p ≥ 0.05) in the water activity values through all storage time. At the end of the storage time, the control had the TVC value of almost near the spoilage limit, while all LA-incorporated patties had significantly (p ≤ 0.05) lower TVC compared with the control. The results revealed high stability in the physicochemical properties as well as total microbial growth during the storage period. The hardness of the LA-incorporated patties was significantly (p ≤ 0.05) lower than that of the control sample. There was no significant (p ≥ 0.05) difference in overall sensory acceptability of the patties made from beef incorporated with food-grade lactic acid compared to the control. This study suggests that incorporating fresh beef with food-grade lactic acid in the mentioned concentrations could result in great benefits of increasing the storage life of fresh beef products with no effect on sensory quality attributes.